2019 16th International Symposium on Wireless Communication Systems (ISWCS) 2019
DOI: 10.1109/iswcs.2019.8877102
|View full text |Cite
|
Sign up to set email alerts
|

NOMA Enhanced Backscatter Communication for Green IoT Networks

Abstract: Backscatter communication has recently emerged as a promising technology to enable the passive sensing-based Internet-of-things (IoT) applications. In a backscatter communication network, uplink transmissions of multiple nodes are usually multiplexed in time-or frequency-domain to avoid collisions, yet it is desirable to improve the uplink capacity further. In this paper, we study a wireless-powered backscatter communication system, where the sensors use a hybrid channel access scheme by combining time divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 13 publications
(14 reference statements)
0
31
0
Order By: Relevance
“…The code-domain NOMA utilizes user-specific spreading sequences to enable the concurrent use of the same resource, while power-domain NOMA exploits channel-gain disparities among users to achieve the same goal and has the advantages of low latency and high spectral efficiency [176]. Therefore, backscatter communication with NOMA has recently been recognized as a promising spectrum-, energyand cost efficient technology for enabling low-power IoT networks [177]- [181]. A hybrid channel access scheme by combining TDMA with power-domain NOMA for multiplexing the backscatter nodes in different regions or with different power levels, has been proposed [177], [181] to enhance the spectrum efficiency, outage probability and throughput of MBCSs.…”
Section: B Multiple-access Schemes and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The code-domain NOMA utilizes user-specific spreading sequences to enable the concurrent use of the same resource, while power-domain NOMA exploits channel-gain disparities among users to achieve the same goal and has the advantages of low latency and high spectral efficiency [176]. Therefore, backscatter communication with NOMA has recently been recognized as a promising spectrum-, energyand cost efficient technology for enabling low-power IoT networks [177]- [181]. A hybrid channel access scheme by combining TDMA with power-domain NOMA for multiplexing the backscatter nodes in different regions or with different power levels, has been proposed [177], [181] to enhance the spectrum efficiency, outage probability and throughput of MBCSs.…”
Section: B Multiple-access Schemes and Protocolsmentioning
confidence: 99%
“…Therefore, backscatter communication with NOMA has recently been recognized as a promising spectrum-, energyand cost efficient technology for enabling low-power IoT networks [177]- [181]. A hybrid channel access scheme by combining TDMA with power-domain NOMA for multiplexing the backscatter nodes in different regions or with different power levels, has been proposed [177], [181] to enhance the spectrum efficiency, outage probability and throughput of MBCSs. Reference [178] considers a NOMA-enhanced ABCS comprising four nodes, namely, the BS, the backscatter device, the nearby cellular user, and the far-away cellular user.…”
Section: B Multiple-access Schemes and Protocolsmentioning
confidence: 99%
“…Since backscatter does not require battery power or or built in power infrastructure, it is an energy efficient communication method for emerging massive wireless networks. Specifically applications like D2D, IoT can be improved further with this scheme [123]. As there are limited research works conducted under energy efficient communications based on NOMA with backscatter, it is a feasible direction for future green wireless networking.…”
Section: Ambient Backscatter Communicationmentioning
confidence: 99%
“…However, the trade-off between enhancing energy efficiency and data rates should be optimized. In the paper [123], a self-powered IoT network with NOMA is presented where the time allocation for wireless power and information transfer stages are optimized under node deployment and constraints for data transmission. M2M communication is a constituent of IoT networks and is becoming a more frequent technology.…”
Section: Internet Of Things (Iot)mentioning
confidence: 99%
“…In conclusion, it was found that NOMA needs more (or equal) DL time than TDMA, while consuming more (or equal) energy and achieving less spectral efficiency. In [14], the authors proposed using NOMA in backsacatter communication (BackCom) for green IoT networks. BackCom is a key enabler technique for wireless power communication networks (WPCN), where power is transmitted to IoT devices through radio frequency (RF) signals.…”
Section: A Power/energy-efficient Resource Allocationmentioning
confidence: 99%